Dermatoglyphics in sports sciences: Understanding the distribution of quantitative indicators in non-athletes and athletes of basketball according to their performance - Borin, J. P.; Padovani, C. R. [UNESP]; Aragon, F. F. [UNESP]; Gonçalves, A. (Centro Andaluz de Medicina del Deporte, 2012)
Objectives. One of the concerns of Sports Sciences is the search for methodologies that can help discover potential athletes. In this sense, some initiatives have been taken in an attempt to identify and characterize the genetic profile of dermatoglyphic marks (fingerprints). The present work has the objective of understanding the distribution of quantitative dermatoglyphic indicators in basketball players with different levels of performance compared to non-players. Methods. The subjects observed constituted 125 individuals, divided into five numerically equal groups, three of which were composed of professional basketball players according to their level of participation (Brazilian Team, National Championship and São Paulo Championship) and the last two formed by weekend players and non-players, respectively. Eleven dermatoglyphic variables were analysed in the descriptive level by means of measurement of position, variability and limits of confidence of the median, and, in inferential terms, the Kruskal-Wallis statistical test was adopted. Results. The more expressive ones were: TRC, counting lines a-b and A'-d, behave differently between athletes and non-athletes. Conclusion. Studies about this kind of analysis should be continued, calling on resources that take into consideration all variables simultaneously as a multivariate study. © 2012 Revista Andaluza de Medicina del Deporte.
Keywords: Athletes; Basketball; Dermatoglyphics; Quantitative indicators